Intergenerational Perspective of the Game as a Cultural Heritage - Araya Góchez, Adriana (2018)
In 2013, the National University of Costa Rica and the University of Costa Rica launched the research project titled Games as a Cultural Heritage: Perception of People of Different Generations in the Cantons of Desamparados and Barva. Its objective was to analyze games as a cultural heritage, from the perception people have of different generational groups in both cantons. This paper presents the results obtained from the intergenerational analysis when contrasting differences and similarities related to the following characteristics of games: conceptualization, importance, values promoted, places where games happen, people involved, and types of games. The research approach was a mix of descriptive and explanatory designs because it provides a sense of understanding the game as a heritage. From Desamparados, 170 people took part in the research; and 158 from Barva. They were primary and secondary students, teachers, adult and senior citizens, and municipal agents. The participants were selected following criteria of age and the role they play. Data were collected using questionnaires that contained common items, and that were based on the generational group. The main results show that all age groups consider games as a pleasurable activity, which promotes fun, entertainment, enjoyment, joy, coexistence and socialization. Games are considered as activities almost exclusively for, and practiced by, boys and girls; a few exceptions mentioned adults and older people as participants in games. Almost the whole population considered games as of extreme importance for integral development, and for the learning of concepts and, essentially, of values. It is striking that games are not considered as a right as set out in the Costa Rican legislation.